Qualitative methodological approach to better understand the socioeconomic factors that influence adoption of Climate-Smart Agricultural options in smallholder farming communities. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The field work was conducted in the Cauca Climate-Smart Village (Colombia) covering direct CCAFS beneficiaries and non-CCAFS-related farmers. A second implementation in Olopa (Guatemala) in support of the CSV monitoring plan, allowed extracting lessons for adjustment which will be reflected in the final version of the methodology in 2019.